Expert System Software to Identify Damages Cars with Forward Chaining Method - Husaini Husaini; Yuswardi Yuswardi (Budapest International Research and Critics University, 2020)
This study shows for the development of expert system software to identify damage to the car that can display information in the form of a solution of the damage. This system was developed using PHP and MySQL software. This system works to be able to present damage identification information on the car that can provide the most actual solution to the consul, as well as present a detailed report when consultations have been made. The purpose of this expert system is to facilitate car users in knowing damage to cars, as well as facilitate car users in identifying damage to cars, so they can update knowledge in the form of symptoms and damage. The diagnosis made by the counselor is: a counselor registers before making the diagnosis. Then answer the questions that have been provided. Furthermore, after making a diagnosis, the results can be printed through the printer.